Delivery Service and Omni-channel Online and Offline in Retailing During the Covid-19 Pandemic - Shu-Hsien Liao; Retno Widowati; Pham Nguyen My Linh (SAGE Open)
Under the Covid-19 pandemic, Vietnam has not only seen in a clear shift from traditional trade to modern trade channels, but also there has been a shift from traditional trade to omni-channel online and offline. This leads to investigate several questions regarding retailing in Vietnam during the Covid-19 pandemic. What omni-channel process of delivery service is provided by operators in Vietnam? What are the profiles of the delivery service for omni-channel consumers in Vietnam? What are different consumer segment delivery service preferences in omni-channel and purchasing modes for online and offline? What profiles/patterns/rules should retail operators consider making their omni-channel delivery service model more competitive for online and offline in retailing? This study investigates Vietnamese consumer behaviors with delivery services and omni-channel online and offline ( N  = 2,204). Data mining analytics, including clustering analysis and association rules, reveal meaningful clusters/patterns/rules for investigating delivery service and omni-channel online and offline development.